Land tenure security for low-income residents’ urban livelihoods : A human development approach review of temporary occupation license - Kiky Kirina, Abdilla; Azima, Abdul Manaf; Abd Hair, Awang (Elsevier Science, Ltd., 2022)
Existing studies on the human development approach discuss how eliminating capability deprivation and enlarging people’s choice led to improvement on their overall wellbeing. However, land tenure security, the precondition to safeguard secure livelihood for poor and low-income urban residents is rarely discussed. This study examines the potential of the human development approach to the land tenure security debate by using a desk review of literature on both concepts. It employs the usage of a land policy instrument, known as the Temporary Occupation License (TOL), which aims to provide urban low-income residents with tenure security despite their lack of formal ownership over the land. In this context, land tenure security is understood from the subjective perspective, rather than from its traditional economic objectives. Findings show that the pursuit of human development through TOL results in an enhanced security of tenure amongst urban low-income residents in two forms. Firstly, protecting them against the threat of eviction through the principle of equity in which TOL provides opportunity for nonlandowners with legal access to state land for housing. Secondly, allowing households to gain the benefits of labour and capital invested in the land. For instance, the principle of efficiency embedded within TOL allows households to utilise land according to their priorities and needs; empowerment allows them to make decisions pertaining to housing and tenure upgrading, whereas sustainability allows citizens and authority to achieve developmental results that benefit both parties. The study concludes that the pursuit of the human development approach in land management, through administrative decisions and conducted in a participatory manner, can indeed enhance land tenure security for urban low-income residents.